Effects of Guanidinoacetic Acid Supplementation on Productive Performance, Pectoral Myopathies, and Meat Quality of Broiler Chickens - Shady Khalil; Nualprae Saenbungkhor; Kajorn Kesnava; Panneepa Sivapirunthep; Ronachai Sitthigripong; Sukanya Jumanee; Chanporn Chaosap (Animals, 2021)
The effects of guanidinoacteic acid (GAA) supplementation on productive performance, pectoral myopathies, and meat quality of broilers were studied. Treatments consisted of corn/soybean-based diets with a GAA supplement (0%, 0.06%, and 0.12%). A total of 546 one-day-old Ross-308 males were randomly allocated to 42 floor pens with 14 replicates (13 birds/pens) for each treatment. The results showed that GAA at doses of 0.06% and 0.12% improved feed conversion, increased the percentage of normal breast, and decreased the severity of wooden breast. Breast muscle myopathy severity was positively correlated with heavy birds and negatively correlated with breast muscle creatine and glycogen. Breast muscle creatine and glycogen correlated positively with normal, less severe pectoral myopathies and meat quality. In conclusion, GAA supplementation improved broiler performance without exacerbating pectoral myopathy or affecting meat quality.
Keywords: Animal Nutrition and Physiology; Meat and Animal Product Quality; Bee Products Chemical Analysis